Integrating the "A" in STEAM: Enhancing STEM learning through stop motion animation - McDaniel, Angela (American Journal of STEM Education, 2026)
This paper explores the integration of the arts ("A") into STEM education through stop-motion animation projects. Stop motion is a dynamic, hands-on medium for students to visually represent complex scientific, technological, engineering, and mathematical processes. By combining storytelling, artistic design, and scientific knowledge, students deepen their understanding of abstract concepts while enhancing creativity and collaboration. One project example illustrates how students model neuronal signal transmission using hand-built neuron models and stop-motion techniques. Additional project ideas are provided to demonstrate the broad applicability of stop-motion across STEM fields. This study highlights the benefits of incorporating artistic expression into STEM education, promoting deeper conceptual understanding and higher student engagement.